Working with Asian Indian American Families: A Delphi Study - Khanna, Anchal; Mcdowell, Teresa; Perumbilly, Sebastian; Titus, Gayatri (Journal of Systemic Therapies, 2009)
In this paper, we contribute to an agenda of developing culturally informed practices, centering specifically on working with Asian Indian and Asian Indian American families. We report the results of a modified Delphi study in which we asked advanced members of the counseling field who are of Asian Indian origin to share their insight relative to family therapy with those who identify as Asian Indian or Asian Indian American in the U.S. Panelists offered a multitude of recommendations, including the importance of: careful assessment that acknowledges within group similarities and differences; attention to extended family ties and intergenerational dynamics; understanding issues of immigration, acculturation, and discrimination; and development of treatment approaches that are congruent with Asian Indian cultural values, beliefs, and practices.
Keywords: dept.mft; peer-reviewed

The Measurement of Outcome Variables in Couple and Family Therapy Research - Sanderson, Jessica; Kosutic, Iva; Garcia, Marisol; Melendez, Tatiana; Donoghue, Jamie; Perumbilly, Sebastian; Franzen, Caroline; Anderson, Stephen (The American Journal of Family Therapy, 2009)
Measurement constitutes a central issue in determining effectiveness of couple and family therapy (CFT). A review of 274 CFT outcome studies published in 25 mental health journals between 1990 and 2005 is presented. Goals of this review were to (1) provide a broad, empirically based overview of CFT outcome research, (2) examine measurement of treatment outcomes, and (3) appraise reporting practices. Findings indicate that a wide range of instruments continue to be used in CFT outcome research, although a foundation for a more integrated and coherent assessment battery has been established. Implications for the field are discussed.
Keywords: dept.mft; peer-reviewed

Undergraduates and intercultural communication competence: Creating a plan for performance - Madlock, A. (International Journal of Learning, 2009)
Some studies indicate that students develop intercultural communication competence through interaction in multicultural classrooms. However, what happens when classrooms are predominately homogenous and student exposure to other cultures is limited to media representations? It is not uncommon to find this situation still existing on some college campuses in the United States of America, where students have never come in contact with individuals different from themselves, beyond service industry workers, if any contact is made at all. The idea of establishing a significant relationship with someone culturally different is not given any thought. As an instructor of color how does one get students to move beyond their comfort zone and take action to meet individuals that are culturally different outside of the classroom? This paper describes the results of a textual analysis using grounded theory of student writing as they reflect on how to develop and implement effective communication strategies with individuals culturally and ethnically different from themselves outside of the classroom. The results of which might also be used to transform thinking about the diverse community surrounding the university and influence future decision-making on issues of social justice and human equality. © Common Ground, Annette Madlock.
Keywords: Grounded theory; Intercultural communication Competence; Multicultural classroom; Textual analysis; Undergraduates; dept.com; ⛔ No DOI found

Saladin and the truth of religion in Decameron I. 3 and X. 9 - Rhodes, J. (Through a Classical Eye: Transcultural and Transhistorical Visions in Medieval Engl. Italian, and Latin Literature in Honour of Winthrop Wetherbee, 2009)
Keywords: dept.eng